A framework for handweaving robotic textiles with liquid crystal elastomer fibers - Sarah Nicita; James C. Weaver; Hiroshi Ishii; Jack Forman (Scientific Reports)
Abstract Textile production methods present a rich set of strategies for developing materials with both form and function encoded at the fiber scale. Beyond simply acting as a static flexible barrier, the ability to incorporate environmentally responsible materials into fabric architectures significantly expands the textile design space by adding on-demand and programmable 3D structural morphing. To this end, liquid crystal elastomers (LCEs) are a promising candidate for enabling these reversible actuation behaviors in fabric-based constructs. Drawing on traditional textile manufacturing techniques and through a detailed exploration of the vast woven textile design space, we have demonstrated programmable and reversible curling, puffing, and in-plane shrinkage behaviors by embedding the functionality of LCE fibers into single and multi-layered woven structures. Predictable shifts in fabric structure directly influence the mechanical properties and the resulting form factor of the actuated textiles, which can in turn be effectively leveraged for the generation of multi-functional devices, enabling new directions for the engineering of flexible stimuli-responsive materials.